1999
DOI: 10.1161/01.cir.100.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cilostazol on Restenosis After Percutaneous Coronary Balloon Angioplasty

Abstract: Cilostazol significantly reduces restenosis and target lesion revascularization rates after successful PTCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(106 citation statements)
references
References 33 publications
5
100
1
Order By: Relevance
“…In addition, the release of platelet-derived growth factors may contribute to smooth muscle cell chemoattraction (into the intima) and proliferation (7). The relevance of these mechanisms to the actual occurrence of stent restenosis has been strongly questioned because clinical trials have failed to document any efficacy of antiplatelets and anticoagulants in preventing restenosis (8,9). DES reduce intimal hyperplasia and restenosis, but they also inhibit stent re-endothelization, making the vessel surface more thrombogenic for longer time periods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the release of platelet-derived growth factors may contribute to smooth muscle cell chemoattraction (into the intima) and proliferation (7). The relevance of these mechanisms to the actual occurrence of stent restenosis has been strongly questioned because clinical trials have failed to document any efficacy of antiplatelets and anticoagulants in preventing restenosis (8,9). DES reduce intimal hyperplasia and restenosis, but they also inhibit stent re-endothelization, making the vessel surface more thrombogenic for longer time periods.…”
Section: Discussionmentioning
confidence: 99%
“…29 -34 Although there is some evidence that controlling mural thrombus formation may decrease neointimal hyperplasia, [35][36][37] antiplatelet agents have not reliably resulted in reductions in restenosis rates in clinical trials. 29,30 Similarly, the systemic administration of corticosteroids aimed at controlling the inflammatory process has not shown decreased restenosis rates.…”
Section: Coated Stentsmentioning
confidence: 99%
“…Tsuchikane et al, with quantitative coronary arteriography (QCA), found significantly less restenosis (p < 0.001), as well as lower rates of target lesion revascularization, larger minimal luminal diameter, and lower percent diameter stenosis for cilostazol versus aspirin in 211 patients after successful PTCA. 26 Another clinical trial in-volving 300 patients randomized to aspirin and ticlopidine, or aspirin and cilostazol, found that cilostazol was as efficacious as the standard regimen in preventing stent thrombosis. 24 A trend toward specific increased drug-related events (e.g., neutropenia) was seen for ticlopidine but not for cilostazol.…”
Section: Introductionmentioning
confidence: 99%